2022
DOI: 10.3390/ijms23031376
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis Due to Hormone Imbalance: An Overview of the Effects of Estrogen Deficiency and Glucocorticoid Overuse on Bone Turnover

Abstract: Osteoporosis is a serious health issue among aging postmenopausal women. The majority of postmenopausal women with osteoporosis have bone loss related to estrogen deficiency. The rapid bone loss results from an increase in bone turnover with an imbalance between bone resorption and bone formation. Osteoporosis can also result from excessive glucocorticoid usage, which induces bone demineralization with significant changes of spatial heterogeneities of bone at microscale, indicating potential risk of fracture. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(135 citation statements)
references
References 106 publications
0
93
0
3
Order By: Relevance
“…Osteoporosis, obesity, and sarcopenia have been studied extensively as individual conditions, and strong evidence has been uncovered for the roles of inflammatory cytokines, such as IL-6, IL-1, and TNF-α, in their pathogenesis [39][40][41]. Osteoporosis represents an imbalance in bone metabolism wherein bone absorption exceeds bone formation [42]. Its development requires the participation of inflammatory cytokines, which promote the formation of osteoclasts from its precursors through a series of signal transduction pathways [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis, obesity, and sarcopenia have been studied extensively as individual conditions, and strong evidence has been uncovered for the roles of inflammatory cytokines, such as IL-6, IL-1, and TNF-α, in their pathogenesis [39][40][41]. Osteoporosis represents an imbalance in bone metabolism wherein bone absorption exceeds bone formation [42]. Its development requires the participation of inflammatory cytokines, which promote the formation of osteoclasts from its precursors through a series of signal transduction pathways [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen binds to the estrogen receptor, which regulates the expression of proteins encoded by estrogen target genes, such as insulin-like growth factor 1 (IGF1) and transforming growth factor-β (TGFβ) [ 41 ]. Studies have shown that estrogen can directly affects cell differentiation and apoptosis [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…New approaches include bone turnover markers to evaluate the therapeutic response [ 43 ] or genetic analysis [ 44 ]. Among elderly individuals, osteoporosis is particularly prevalent in postmenopausal women, mainly due to estrogen deficiency [ 45 ]. However, long-term corticoid treatment and systemic diseases affecting bone formation and turnover (such as diabetes, chronic kidney diseases, multiple myeloma, primary hyperparathyroidism or immobilization) are also relevant factors leading to osteoporosis [ 46 ].…”
Section: Risk Factorsmentioning
confidence: 99%